A consensus document for the clinical management of invasive fungal diseases in pediatric patients with hematologic cancer and/or undergoing hematopoietic stem cell transplantation in Brazilian medical centers - Carlesse,Fabianne (2019)
ABSTRACT In the present paper we summarize the suggestions of a multidisciplinary group including experts in pediatric oncology and infectious diseases who reviewed the medical literature to elaborate a consensus document (CD) for the diagnosis and clinical management of invasive fungal diseases (IFDs) in children with hematologic cancer and those who underwent hematopoietic stem-cell transplantation. All major multicenter studies designed to characterize the epidemiology of IFDs in children with cancer, as well as all randomized clinical trials addressing empirical and targeted antifungal therapy were reviewed. In the absence of randomized clinical trials, the best evidence available to support the recommendations were selected. Algorithms for early diagnosis and best clinical management of IFDs are also presented. This document summarizes practical recommendations that will certainly help pediatricians to best treat their patients suffering of invasive fungal diseases.